Moldova : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments in the Republic of Moldova during 1992-96. The authorities embarked on a comprehensive program of financial stabilization beginning in 1993. By 1995, the fiscal deficit had been cut to 5 1\2 percent of GDP and the National Bank had implemented a tight monetary policy. Output stabilized and exports and imports rose rapidly, with the current account deficit narrowing to 6 1\2 percent of GDP from 13 1\2 percent in 1993. Data for the first half of 1996 show inflation remaining low and output recovering.